Roadside Boundary Perception for Autonomous Driving using Machine Learning techniques on Radar Reflections - Leuthner, Maren Corina (2021)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science